The Domestic and Foreign Price Gaps in the P-STAR Model : Evidence from Spain - Garcia-Herrero, Alicia (IMF Working Papers; Working Paper ;, 1999)
The paper uses the P-STAR model to analyze Spanish prices from 1970 to 1996, adding the foreign price gap to the standard domestic definition of the P-STAR model (the domestic price gap) to assess the role German price movements played in Spanish inflation. The domestic price gap turns out to be the major explanatory variable for inflation, even after the entrance of Spain in the exchange rate mechanism (ERM). This result suggests that the successful disinflation experienced in Spain in the past few years may be more related to domestic conditions than to foreign ones.